Dynamic and Contact Characteristic Analysis of Flexible Bearing of Harmonic Gear Drive based on Finite Element - Zhang Dongliang; Liu Fei (Jixie chuandong)
To the problems of flexible bearing has an important effect on the carrying capacity,transmission accuracy and life of the harmonic gear drive,a flexible bearing is regarded as the research object,the dynamic and contact characteristics of flexible bearing are analyzed based on ANSYS/LSDYNA nonlinear contact analysis method for comprehensive consideration of the factors such as bearing rotating speed,load and deformation and so on.The results show that the dynamic characteristics of flexible bearing outer ring in different positions are basically the same,the moved distance of rolling in long axis different distance is basic same,the velocity wave troughs alternating changes and the velocity decreases with increasing distance.The outer ring,rolling body stress concentrated near the long axis,stress wave troughs alternating changes,the stress value decreases away from the long axis;the rolling element and contact force on inner and outer is volatile,and basically the same with external load,and the keep contact force size is less volatile.